Weed Vegetation Analysis Based on Sdr and Ivi in Peanut (Arachis hypogaea L.) Fields of Cipocok Jaya District, Serang - Kurniasari, Amelia Dwi; Hermita, Nuniek; Rumbiak, Julio Eiffelt Rossaffelt; Putri, Widia Eka (Jurnal Agroekoteknologi Terapan, 2026)
Peanuts (Arachis hypogaea L.) play an important role as an agricultural commodity with high economic value and are a source of protein in the community's consumption patterns. This study aims to identify the dominant weed species based on Summed Dominance Ratio (SDR) and Importance Value Index (IVI) in peanut (Arachis hypogaea L.) cultivation areas. The research was conducted from August to October 2025 on farmer group land in Link Beberan, Banjaragung Village, Cipocok Jaya Subdistrict, Serang City, Banten Province. This study used a quadrat method with random sampling plot placement measuring 1 × 1 m2 at 20 observation points. The results found 15 weed species from 8 family with a total of 614 individuals consisting of grass weeds and broadleaf weeds. The weed found in almost all research plots was Rottboellia cochinchinensis with 241 individuals/m2 and a relative value of 39.22%, while the lowest was found in the species Eriochloa with 1 individual/m2 and a relative value of 0.16%. The highest relative frequency value was found in Rottboellia cochinchinensis and Richardia brasiliensis at 20.83%. The highest Importance Value Index (IVI) obtained on peanut fields was 89.10, found in the weed species Rottboellia cochinchinensis. The most dominant weed was Rottboellia cochinchinensis with an Summed Dominance Ratio (SDR) value of 29.03. Weed diversity was classified as medium (H′ = 1.58). The results of the study indicate that differences in the level of dominance between species reflect the relationship between the biological characteristics of weeds and local environmental conditions. Keywords: Weeds, Frequency value, Summed Dominance Ratio (SDR), Importance Value Index (IVI), Peanut plant.